2021
DOI: 10.1007/s00779-021-01520-9
|View full text |Cite|
|
Sign up to set email alerts
|

The early warning research on nursing care of stroke patients with intelligent wearable devices under COVID-19

Abstract: Stroke patients under the background of the new crown epidemic need to be home-based care. However, traditional nursing methods cannot take care of the patients' lives in all aspects. Based on this, based on machine learning algorithms, our work combines regression models and SVM to build a smart wearable device system and builds a system prediction module to predict patient care needs. The node is used to collect human body motion and physiological parameter information and transmit data wirelessly. The softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…One of the included studies reported that the application of wearable devices can enhance recovery among patients with stroke. 20 The result findings are congruent with a study of symptom tracking https://doi.org/10.2147/JMDH.S459946…”
Section: Dovepresssupporting
confidence: 83%
See 3 more Smart Citations
“…One of the included studies reported that the application of wearable devices can enhance recovery among patients with stroke. 20 The result findings are congruent with a study of symptom tracking https://doi.org/10.2147/JMDH.S459946…”
Section: Dovepresssupporting
confidence: 83%
“…One of the included studies reported that the application of wearable devices can enhance recovery among patients with stroke. 20 The result findings are congruent with a study of symptom tracking in endometriosis using digital technologies, which aims to discuss how digital technologies may be used in endometriosis to facilitate symptom tracking. 58 The study suggested that objective measures extracted from wearable devices can be integrated with self-reported symptom measures to provide insight into symptom trajectories and the association between objective behaviors and subjective symptoms.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations